Influence of lower quarter Y-balance test™ screening protocol on dynamic balance outcomes - Lawrance, S.; Jacobs, M.; Boss, E.; Popp, J.; Leverenz, L.; Weller, M. (British Journal of Sports Medicine, 2021)
Background The Lower Quarter Y-Balance Test™ (LQYBT) is commonly used to determine risk of injury or readiness for return to sport. However, clinicians conduct the assessment with differing test protocols potentially altering test outcomes.